SOCIAL-ECONOMIC DEVELOPMENT PROGRAMS OF THEIR FUNDING DIRECTIONS TERRITORIES - Abraev, Farrukh (THE INNOVATION ECONOMY, 2024)
In order to increase the effectiveness of the funds directed to the socio-economic development programs of the regions, the issues of increasing the control based on the transfer of the authority to make changes to these expenses to the discretion of the local councils, focusing the priority on the financing of the socio-economic development programs of the regions in the use of additional sources of income of the local budgets are covered in this article.